Uso da própolis nos valores de perfil metabólico em ovelhas sob diferentes dietas, no pré e pós-parto - Rodrigues, Tatiana Fiorotti (2013)
The objective of this study was to evaluate the action of propolis in the feeding of ewes in pre and post-partum phases and the animal response by plasma concentrations of some blood metabolites. Four treatments were studied, using 16 animals divided in four groups. The treatmens were: Control treatment (TC), control diet; Flushing treatment (TF) control diet with flushing; Flushing Treatment with propolis level 1 (TFP1), control diet with flushing and 20 ml of alcoholic solution of propolis/animal/day and ; Treatment Flushing with level 2 of propolis (TFP2) diet control and flushing with 30 mL of alcoholic solution of propolis/animal/day. The animals were kept in stalls and fed over a period of 37 days, seven of the control diet adaptation and 30 days of blood sampling. Were fed twice a day at 7 AM y 16PM, samples were taken at three-day and one hour before the delivery of food and one and three hours after feeding. There were significant differences among treatments for albumin, which were within normal range, and for globulins, which values were below those considered normal. Aspartate transaminase enzyme presented a significant difference between the phases, before and after birth, but with normal values. Propolis extract did not affect urea and total proteins, however resulted in changes on albumin and globulin levels